中国农村城市化进程主要障碍因素解析 = An aanalysis on urbanization of rural China - 魏四海 Wei, Sihai (2008)
This paper studies the deviation of urbanization process from the industrialization in China. On principles of urban economics, the paper suggests a theory of industrial location choice, based on three major factors that will influence the enterprises’ choice of location: rent of land, transport cost, and social cost.